2014
DOI: 10.1097/sla.0000000000000960
|View full text |Cite
|
Sign up to set email alerts
|

New-onset Atrial Fibrillation Post-surgery for Esophageal and Junctional Cancer

Abstract: A total of 473 patients (mean age: 63 years; 73% male) underwent resection, 51% 2-stage, 18% 3-stage, 12% transhiatal, and 19% extended total gastrectomy. Ninety-six (20%) patients developed new-onset AF, in 18%, 27%, 29%, and 14% of 2-, 3-, transhiatal, and extended total gastrectomy cohorts, respectively (P=0.05). Age, diabetes, neoadjuvant therapy, and cardiac history predisposed (P<0.05) to AF, and AF was significantly (P<0.0001) associated with pneumonia, pleural effusions requiring drainage, and maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 47 publications
5
45
3
Order By: Relevance
“…13,23 Moreover, we confirmed the negative impact of malnutrition on POM. 24 Therefore, these results advocate for the importance of conditioning and rehabilitation before esophagectomy, with screening and correction of malnutrition, smoking cessation, and preoptimization of pulmonary and cardiac conditions.…”
Section: Discussionsupporting
confidence: 89%
“…13,23 Moreover, we confirmed the negative impact of malnutrition on POM. 24 Therefore, these results advocate for the importance of conditioning and rehabilitation before esophagectomy, with screening and correction of malnutrition, smoking cessation, and preoptimization of pulmonary and cardiac conditions.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of adenocarcinoma of the esophagus and gastroesophageal junction has risen significantly in recent years, particularly in the West [1]. It carries a poor prognosis, with an overall 5-year survival of approximately 15%, and approximately 40% in patients who can be treated with curative intent [2,3]. Moreover, operative morbidity is high, and the risk of in-hospital mortality even in the best-reported series is up to 5%.…”
Section: Introductionmentioning
confidence: 99%
“…Between March 2013 and January 2016, 128 patients were scheduled to undergo oesophagectomy for thoracic oesophageal cancer. Of these, 28 were excluded from the study on POD 1 before randomization because of failure to meet the inclusion criteria (24), complication with an intraoperative aortic injury (1), need for reoperation for diaphragmatic hernia (1) and refusal to participate (2). The remaining 100 patients were randomized; 50 patients were treated with 5 per cent glucose solution (placebo group) and 50 received landiolol (landiolol group) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Oesophagectomy for cancer is high-risk surgery with considerable morbidity and mortality 1,2 . New-onset atrial fibrillation (AF) after oesophagectomy has been reported, with a variable incidence of 9-46 per cent 2 -8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation